Multichannel service failure and recovery in a O2O era: A qualitative multi-method research in the banking services industry - Reis, João (2020)
This article aims to investigate how service providers are employing their channels to support the handling of customer complaints in an online to offline era. It provides a timely contribution by characterizing multichannel recovery practices, discussing its implications for customers, and discovering new trends. The study employs a qualitative multi-method research, which includes not only more than one method of collecting data, but also more than one method of analyzing data. Data collection involved 50 records of customer complaints, 10 semi-structured interviews, direct observation and internal bank reports. The results suggest that multichannel customers are not willing to interact with a large number of channels to solve their problems leading to a high number of interactions. Customers expect a complex recovery not in terms of interactivity but in terms of depth. Recovery solutions, such as apologizing and monetary compensations are non-permanent solutions, are inefficient in the long term and imply financial losses. Despite the investment that is required, this investigation advocates for permanent solutions. To avoid service failures and complex recovery processes, it is possible that companies are improving their operations management in search of new strategies that are blurring the boundaries of O2O into a mix of offline and online channels (O2).